Policy innovations and effective local management of forests in the Philippine Cordillera region - Mendoza, Lorelei Crisologo (Cordillera Review : Journal of Philippine Culture and Society, 2009)
With the passage of the Indigenous Peoples' Rights Act of 1997, the tenurial rights of ancestral domains for indigenous peoples in the Philippines are now a legal reality (Leonen 1998). While it is necessary to recognize indigenous peoples' land rights to achieve sustainable forest management in the Cordillera Region of northern Luzon because of the importance of property rights to convey authority and shape incentives for the management of natural resources, as Meinzen-Dick and Knox (2001, 49) assert, this would not be sufficient. Since management technologies and practices affecting forests cover a larger spatial scale and a longer time horizon, security of tenure is important. However, collective action is also needed. Forests need to be protected from fire or encroachment, maintained through replanting, and monitored to prevent over-harvesting. For local users and communities to participate in these activities, they must be assured that the benefits will redound to them and their children, hence the importance of secure tenure. But although collective action is reinforced by property rights, more is required. Collective action prospers in an enabling environment that in part consists of policies that create legal standing for organizations at the community level which come into agreements with government agencies (see Meinzen-Dick and Knox 2001). The enabling environment for collective action will include local government support for user groups, and decision making processes of national level agencies that encourage and protect the community's right to manage natural resources.